Aplicação da tecnologia de membranas poliméricas para purificação de biogás - Trentin, Vânia Maria (My University, 2017)
The high dependence on fossil fuels to supply the world's energy needs is causing serious environmental problems which are mainly related to climate change, due to the increased greenhouse gas emissions. In this context, the need to pursuit emerging renewable energy sources to meet the existing demand arises. The biogas generated from the anaerobic digestion of biomass emerges as a promising alternative to the current non-renewable energy sources. However, so that the biogas can be used as energy and heat its purification becomes necessary in order to remove the impurities and to increase its efficiency for use. The establishment of gas separation technologies on the industrial market, specially the membranes processes, can be one way to improve the alternative energy generation processes. This energy can be used later with minimum impact to the natural ecosystem, where the human being is inserted. Given the background, in this work the characterization of polymeric commercial membranes was performed. Different analytical methods were used in order to know the morphological properties of the polymeric material for the use in gas purification processes. Gas permeation experiments were conducted using in laboratory and industrial scale permeation tests using commercial membranes of poly (dimethylsiloxane) (PDMS) and Polysulfone developed by the Laboratory of Research in Materials Chemistry (UCS) in order to evaluate permeability and selectivity of the membranes for the desired purpose. For laboratory scale tests, pure gases and standard mixtures of CO2 and CH4 were used. In an industrial plant, raw biogas of anaerobic digestion were used. The membranes were characterized by TGA, DSC, FTIR and MEV and as to permeability and selectivity. Commercial membrane analysis (PDMS) showed that the backing layer is composed of polyester and not Polysulfone as specified by the manufacturer. PSf 10'E membrane presented the highest permeability to pure CH4 (122.8 Barrer), while PSf 20'E showed the highest permeability to pure CO2 (307,0 Barrer). The PDMS membrane was highlighted with a higher permeability, ranging from 3.164 to 12.065 Barrer. The permeability tests using PDMS membranes showed the best results in the gas separation (better selectivity) at 6.0 kgf.cm-2 in laboratory scale, where it obtained 9.7 mols of CO2 and 0.10 mols of CH4 in the permeated for analisys with standard gas mixture 70% CH4 and 30% CO2. In the industrial scale, it was not possible to obtain results due to the presence of H2S in the feed as well dirt, which caused the fouling phenomenon, besides the oxidation of the polymeric materials and rupture of the PDMS membrane.
A elevada dependência de combustíveis fósseis para o abastecimento das necessidades energéticas mundiais vem causando inúmeros problemas ambientais, principalmente relacionados às mudanças climáticas, devido à crescente emissão de gases poluentes ao meio ambiente. Nesse contexto, surge a necessidade emergente de busca por fontes de energia renováveis para atender a demanda mundial. O biogás, proveniente da digestão anaeróbia de biomassa, torna-se uma alternativa promissora em relação às energias não renováveis existentes. No entanto, para que o biogás possa ser aproveitado na forma de energia e calor, se faz necessário sua purificação, a fim de remover as impurezas e aumentar sua eficiência. A introdução no mercado industrial de tecnologias de separação de gases, mais especificamente, do uso de membranas, é um dos meios de melhorar os processos de geração de energia alternativa que podem ser utilizadas posteriormente, com o mínimo impacto ao ecossistema natural, no qual o ser humano encontra-se inserido. Nesse contexto, no presente trabalho, foi realizada a caracterização de membranas poliméricas comerciais por meio de diferentes métodos de análise, a fim de se conhecer as propriedades morfológicas do material para aplicação em processos de purificação de gases. Foram realizados ensaios de permeação em escala laboratorial e em escala industrial, utilizando membranas comerciais de poli (dimetilsiloxano) (PDMS) e, de Polisulfona (PSf) desenvolvidas pelo Laboratório de Pesquisa de Química dos Materiais (UCS), a fim de avaliar a permeabilidade e a capacidade seletiva das membranas para a finalidade desejada. Para os ensaios em escala laboratorial, foram utilizados gases puros e misturas padrão de CO2 e CH4. Em planta industrial, foi utilizado biogás pré-tratado de digestão anaeróbia de produtos alimentícios. As membranas foram caracterizadas por Tg, DSC, FTIR, MEV e, quanto a permeabilidade e seletividade. As análises da membrana comercial (PDMS) mostrou que a camada suporte é composta de poliéster e não de Polisulfona conforme especificação do fabricante. A membrana PSf 10’E apresentou a maior permeabilidade ao CH4 puro (122,8 Barrer) enquanto a PSf 20’E apresentou maior permeabilidade para CO2 puro (307,0 Barrer). A membrana de PDMS destacou-se com a maior permeabilidade, com variação de 3164 a 12065 Barrer. Os ensaios de permeação utilizando membranas de PDMS apresentaram os melhores resultados na separação de gases (melhor seletividade) a 6,0 kgf.cm -2 em laboratório, onde foi obtido foi de 9,7 mols de CO2 e de 0,10 mols de CH4 no permeado para a mistura padrão 70%CH4 e 30% CO2. Em escala industrial, não foi possível obter resultados devido a presença de H2S na alimentação, bem como de sujidades, que provocaram o fenômeno de fouling, além da oxidação dos materiais poliméricos e ruptura da membrana de PDMS.
Keywords: Biogás - Purificação; Tecnologia; Ciências ambientais; Álcool; Biogas - Purification; Technology; Environmental sciences; Alcohol